Family Vulnerability and Children’ Nutritional Status during COVID-19 Pandemic - Yusuf, Andi Mukramin; Tenrisau, Dhihram; Hidayanti, Healthy; Ibrahim, Abdul Haris; Bahar, Ardiansyah; Sarifudin, Sarifudin; Tahir, Yoesrianto; Adhyanti, Adhyanti; Alfiah, Elma (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2022)
Introduction: COVID-19 infected millions of people and became the main mortality worldwide. COVID-19 also affected other health problems, including nutritional problems. This study aimed to find the factors that affected the nutritional and socio-economic status during the COVID-19 pandemic in a neighborhood of DKI Jakarta.Methods: This study utilized a cross-sectional design. Total sampling method on all families who had children in the 9th Neighborhood, Cawang Sub-District, DKI Jakarta was used. A total of 72 families were involved in this study, and the informants of this study were mothers of under five children. This study utilized a modified questionnaire from the Indonesian National Socio-Economic Survey (Susenas) and the Indonesian Nutritional Status Study (SSGI). This study utilized bivariate and multivariate logistic regression analysis.Results: From all of 72 families with children, it was found that eight children were wasting. The Job-Loss (PHK) has an OR of 37.8 (95%CI: 5.87-748.53; p=0.001), while below poverty line had an OR of 14.24 (95%CI: 3.55-170.35; p=0.004) to be wasted. The multivariate analysis had included covariates such as parental occupation, parental education, and antenatal care (ANC). Job-Loss and Below Poverty Line were the main factors in increasing the risk of malnutrition cases after controlled by covariates. Conclusion: The decrease in socio-economic status of a family during the pandemic, increased the risk of wasted children. Improvements in policy interventions and socio-economic aids are necessary to improve the nutritional status of under five children in the lower-middle class during the COVID-19 pandemic.